التشيُّع في ماليزيا: مراجعة أولية: (Shi’ism in Malaysia: A Preliminary Review) - Bin Mohd Amin (وان محمد عزام محمد أمين) Wan Mohd Azam; B. Muhamad Shukri (عبد السلام @ ذو الكفل بن محمد شكري) Abdul Salam @ Zulkifli; Artalim (منتهى أرتاليم) Muntaha (At-Tajdid - Intellectual Refereed Journal, 2019)
Abstract The research aims at a generally explaining the history of Shi’ism in Malaysia including its development, its causes and its influence in the creed of Malay Muslim community in Malaysia. The study uses the analytical approach to review texts related to Shi’ism in Malaysia, conducting interviews with selected Shiite followers and ties sympathizers. Among the conclusions are: that the appearance of Shi’ism in Malaysia was the aftermath of the Iranian Revolution in 1979. This had led to some tensions between them and the local religious authorities in Malaysia. Eventually this had led to the banning of Shia in 1996 though the number of its followers keep on increasing day by day. Keywords: Shi’ism, Shī‘ah, Malaysia, Malaysian society.